2019
DOI: 10.7717/peerj.8140
|View full text |Cite
|
Sign up to set email alerts
|

Sarc-F and muscle function in community dwelling adults with aged care service needs: baseline and post-training relationship

Abstract: BackgroundThis study sought to better understand the psychometric properties of the SARC-F, by examining the baseline and training-related relationships between the five SARC-F items and objective measures of muscle function. Each of the five items of the SARC-F are scored from 0 to 2, with total score of four or more indicative of likely sarcopenia.MethodsThis manuscript describes a sub-study of a larger step-wedge, randomised controlled 24-week progressive resistance and balance training (PRBT) program trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In support of this hypothesis, SARC-F is inversely associated with objective measures in strength and physical performance, including reductions in grip strength and gait speed as well as increases in the Timed Up and Go (TUG) Test and 5 chair stand test. [37][38][39][40][41] Of note, myosteatosis but not sarcopenia was significantly associated with decreased overall survival in our study. This is consistent with prior studies demonstrating that muscle quality, rather than muscle quantity, may better predict mortality, presumably because of its closer association with physical function.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…In support of this hypothesis, SARC-F is inversely associated with objective measures in strength and physical performance, including reductions in grip strength and gait speed as well as increases in the Timed Up and Go (TUG) Test and 5 chair stand test. [37][38][39][40][41] Of note, myosteatosis but not sarcopenia was significantly associated with decreased overall survival in our study. This is consistent with prior studies demonstrating that muscle quality, rather than muscle quantity, may better predict mortality, presumably because of its closer association with physical function.…”
Section: Discussionsupporting
confidence: 42%
“…Although the mechanisms underlying this observation are unclear, we hypothesize that SARC‐F is at least partially capturing the functional components of low muscle strength and/or poor physical performance. In support of this hypothesis, SARC‐F is inversely associated with objective measures in strength and physical performance, including reductions in grip strength and gait speed as well as increases in the Timed Up and Go (TUG) Test and 5 chair stand test 37–41 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Based on simplicity and clinical relevance of the recommendations of the EWGSOP2, we would recommend that the oncology healthcare teams should routinely assess SARC-F and/or handgrip strength test (Cruz-Jentoft et al, 2019), with such assessments only taking a handful of minutes to complete. It is even possible that the SARC-F monitoring could be performed by the patient themselves, as a recent study demonstrated that changes in older adults' SARC-F scores match that of quantitative assessments of muscle strength and physical performance performed by their allied health professionals (Keogh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%